2020
DOI: 10.4274/tjod.galenos.2020.89896
|View full text |Cite
|
Sign up to set email alerts
|

Do external female genital measurements affect genital perception and sexual function and orgasm?

Abstract: Amaç: İn vitro fertilizasyon (İVF) ve embriyonik manipülasyonlar yoluyla gebe kalan kadınlarda hormon kullanımı, pulmoner hipertansiyon olasılığı da dahil olmak üzere yenidoğanların sağlığıyla ilgili endişeleri artırmıştır. Bu nedenle bu çalışma, term İVF yenidoğanlarında pulmoner arter basıncını değerlendirmeyi amaçlamıştır. Gereç ve Yöntemler: Bu prospektif kesitsel çalışma Mart 2013 ile Ekim 2017 arasında gerçekleştirilmiştir ve 160 İVF yenidoğanı (grup 1) 160 doğal yolla olan yenidoğanla (grup 2) karşılaşt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In our study, we found that one‐fifth of the participating women were dissatisfied and ashamed of their genitalia and 21.3% of our female population would consider undergoing cosmetic genital surgery. Another prospective cohort study from Turkey showed that although genital measurements and genital perceptions varied among participants, a relation was not found between genital measurements and sexual functions, suggesting that a more cautious approach should be taken towards genital surgeries for cosmetic purposes 17 …”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that one‐fifth of the participating women were dissatisfied and ashamed of their genitalia and 21.3% of our female population would consider undergoing cosmetic genital surgery. Another prospective cohort study from Turkey showed that although genital measurements and genital perceptions varied among participants, a relation was not found between genital measurements and sexual functions, suggesting that a more cautious approach should be taken towards genital surgeries for cosmetic purposes 17 …”
Section: Discussionmentioning
confidence: 99%
“…Women undergoing FGCS are within the normal variability of function and anatomy, however, they have the right to choose according to their desires, although the burden of such interventions relies on health professionals [14]. There is lack of knowledge about what constitutes normal regarding sexual function and anatomy, so preoperative counseling about genital diversity and correction of genital perception may prevent unnecessary procedures [9,11,14]. Cosmetic gynaecology procedures should be tailored by health professionals to achieve and design the most appropriate strategy [10].…”
Section: Discussionmentioning
confidence: 99%
“…Biological (such as neurogenic, anatomical, hormonal, vascular) and psychosocial factors (such as disturbed body image perception, depression, anxiety, and some other medical conditions that may decrease sexual confidence) play a decisive role [8]. Approximately 41% of females of reproductive age present with sexual dysfunction [9,10,11]. Although the diversity in genital anatomy is wide, recently the population of women seeking FGCS procedures, notably vaginal rejuvenation, has increased tremendously [1,2].…”
Section: Current Opinion In Gynecology and Obstetricsmentioning
confidence: 99%
“…Although there are substantially less data than for the high-androgen population, the average length of the clitorophallus in a low-androgen population has been reported as ranging from 3 to 1.2 cm. [41][42][43]…”
Section: The Clitorophallus At the Time Of Pub Ert Ymentioning
confidence: 99%